MALIGNANCY IN BABYLON ONCOLOGY CENTERS (1990 - 2018) - Al-Alawachi, Sharif Fadhil; Alwash, Rida Muhi; Mohsin, haider; Ameir, Wisam Abdul; Al-Dahmoshi, Hussein Oleiwi; Helmi, Ali; Sharif Al- Alawchi, Mohammed Saeed; Al-Alawchi, Ali Sharif (International Journal of Psychosocial Rehabilitation, 2020)
During the period (1990 – 2018 ) 18686 cases of malignancy were reported in Merjan Medical City Oncology Center as following :- 8634 (46.20%) cases were male and 10052 (53.79%) cases were female with the ratio of M: F equal to 1:1.15 It is concluded that the incidence of cancer is increasing in alarming way in the last (28) years. It is mainly due to the effect of Air, Water and Earth Pollution by the previous Wars on Iraq. This increasing incidence of cancer is associated with a younger age group especially with regard to Breast and Colonic carcinoma. However, high percentage of those malignant patients got good benefit by treatment with chemotherapy and /or Hormonal therapy in Babylon oncology center.The patients who need Radiotherapy were treated in Baghdad Radiotherapy Institute previously because the radiotherapy machines was under establishment in Babylon & in south of Iraq till the beginning of 2016 .